A micromechanical relaxation model of composite bolted connections based on viscoelastic theory. (20th June 2016) - Wang, Jingze; Li, Yanqi; Dai, Fuhong
Abstract: A micromechanical model to predict the stress relaxation of composite bolted connections based on viscoelastic theory has been presented. A number of experiments were conducted to validate the model. The influence of the initial clamp forces and the plate thicknesses of GFRP and CFRP on the stress relaxation were investigated. The stress relaxation predicted showed a good agreement with the experimental data with the deviation of about 6%. It shows that there exists a certain time, which is approximately 5 times of the relaxation time, and the contribution of the composites' viscoelasticity could be ignored when the time is greater than the certain time. The loss of the clamp forces was primarily caused by the increase in plasticity.